Special Issue Dedicated to Late Professor Takuo Okuda. Tannins and Related Polyphenols Revisited: Chemistry, Biochemistry and Biological Activities - Yoshida, Takashi (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Antioxidative polyphenols represented by tannins and flavonoids are rich in numerous food sources and traditional natural medicines and currently attracting increased attention in health care and food industries because of their multiple biological activities that are favorable to human health. Commemorating the outstanding achievements on tannins by Dr. Takuo Okuda on the occasion of his passing away in December 2016, his colleagues, friends, and worldwide experts of polyphenol research have contributed 18 papers on their recent study to the Special Issue of Molecules. This book is its reprinted form. This covers reviews of structural features, historical usages, and biological activities of unique class of ellagitannins and condensed tannins, and original articles on the most up-to-date findings on the anticancer effect of green tea catechins, the antivirus effect of tannins comparing with the clinically used drugs, the analytical method of ellagitannins using quantitative NMR, the chemical structures of Hydrangea-blue complex (pigment) and condensed tannins in Ephedra sinica and purple prairie clover, and the relationship of condensed tannins in legumes and grape-marc with methane production in the in vitro ruminant system, and others. This book will be useful to natural product chemists and also to researchers in pharmaceutical and/or food industry.